Kebudayaan Populer di Era Milenial: Pengaruh Media Sosial Terhadap Identitas Generasi Z - Rahmawati, Kurnia (Maliki Interdisciplinary Journal, 2025)
This article discusses the influence of popular culture and social media on the identity of Generation Z in Indonesia. Generation Z, born between 1997 and 2012, is a generation that grew up in the midst of the technological and internet revolution. They exhibit characteristics such as openness to differences, a critical attitude toward information, and a strong desire for freedom and independence during the process of forming their personal identity. Social media and online platforms have played a crucial role in spreading this trend, which includes popular culture such as music, movies, fashion, and lifestyle, including the idea of metrosexuals. Social media is also crucial for Gen Z to express their local identity through language, music, dance, and traditional clothing, often by cleverly combining local elements and international trends. Gen Z has not lost its identity due to foreign popular culture influences that bring foreign elements; Instead, they are able to blend elements of popular culture with the richness of local culture, resulting in a unique and diverse identity. Generation Z faces the challenge of maintaining Indonesian cultural values amid the current of globalization in a situation like this, but they also have a great opportunity to promote local culture to the global level through online platforms like TikTok. To navigate the diverse information landscape and shape their understanding, Gen Z needs "informative" skills, or information literacy. Information literacy refers to the ability to know when, why, where, and how to evaluate, use, and communicate information ethically. By maintaining a balance between appreciation for local cultural heritage and adaptation to international trends, Generation Z plays an important role in determining the future of Indonesia's national identity.